2020
DOI: 10.1007/s42770-020-00321-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and phylogenetic analysis of SARS-CoV-2 and hosts ACE2 protein suggest Malayan pangolin as intermediary host

Abstract: An emergence of a novel coronavirus, causative agent of COVID19, named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), occurred due to cross-species transmission. Coronaviruses are a large family of viruses able to infect a great number of hosts. Entrance of SARS-CoV-2 depends on the surface (S) protein interaction with host ACE2 protein and cleavage by TMPRSS2. ACE2 could be a species-specific barrier that interferes with bat-to-human coronavirus cross-species transmission. Molecular analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…One explanation is that bat-nCoV was transmitted from bat to pangolin by chance, and got recombined with pangolin-nCoV in pangolin, after which the new recombined virus acquired the ability to invade human cells. Lopes et al (2020) regarded the ACE2 as the barrier for cross-species transmission and conducted a host evolutionary analysis of ACE2 sequence. They found the evolutionary divergence between pangolin ACE2 and hACE2 is relatively lower than that between bat ACE2 and hACE2 ( Lopes et al, 2020 ).…”
Section: Wildlife As the Potential Intermediate Hostsmentioning
confidence: 99%
“…One explanation is that bat-nCoV was transmitted from bat to pangolin by chance, and got recombined with pangolin-nCoV in pangolin, after which the new recombined virus acquired the ability to invade human cells. Lopes et al (2020) regarded the ACE2 as the barrier for cross-species transmission and conducted a host evolutionary analysis of ACE2 sequence. They found the evolutionary divergence between pangolin ACE2 and hACE2 is relatively lower than that between bat ACE2 and hACE2 ( Lopes et al, 2020 ).…”
Section: Wildlife As the Potential Intermediate Hostsmentioning
confidence: 99%
“…Similarly, recent studies have shown that SARS-CoV-2 might originated from bats with the genome of SARS-CoV-2 has 88%–96% (91% on average) nucleotide identity with several bat coronaviruses and 79%–82% (80% on average) with human SARS-CoV, but might with more proximal origins from a potential intermediate animal host ( Chan et al, 2020 ; Ji et al, 2020 ; Lu et al, 2020 ; Zhou et al, 2020b ). It has been reported that pangolins ( Lam et al, 2020b ; Lopes et al, 2020 ; Wahba et al, 2020 ; Xiao et al, 2020c ; Zhang et al, 2020b ) and snakes ( Ji et al, 2020 ) might be the intermediate hosts of SARS-CoV-2. However, the possibility of snakes as intermediate hosts of SARS-CoV-2 was questioned by the scientific community ( Zhang et al, 2020b ), and the existing evidence was not sufficient to either confirm or rule out the role of pangolins as an intermediate host ( Tiwari et al, 2020 ; Wahba et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2, the pathogenic factor for COVID-19, is a novel zoonotic RNA betacoronavirus. Several studies have conducted phylogenetic analyses of SARS-CoV-2 to determine its sequence homology with other viruses of the family Coronaviridae [4] , [14] , [15] , [16] , [17] , [18] . It has been reported that SARS-CoV-2 shares a 79.6% sequence homology with SARS-CoV, and 96.2% resemblance with bat coronavirus (HKU4) [14] .…”
Section: Virologymentioning
confidence: 99%